Improving traffic safety (Academic Journal of Internal Affairs, 2011)
This author provides several recommendations for improving traffic safety and preventing and motoring traffic violations. These include life-long teaching and learning of traffic rules as well as the involvement of civil guard services in accident and crime prevention.
Keywords: transport; safety; prevention